Thrombo-Inflammatory Prognostic Scores Improve BISAP-Based Risk Stratification in Acute Pancreatitis Patients: A Retrospective Cohort Study - Han T; Cheng T; Liao Y; Lai Q; Tang S; Liu B; He Y; Lei C; Cao Y; Cao Y (Journal of Inflammation Research, 2022)
Tianyong Han,1,* Tao Cheng,1,* Ye Liao,2 Qiang Lai,1 Shiyuan Tang,1 Bofu Liu,1 Yarong He,1 Chenxi Lei,1 Yuling Cao,3 Yu Cao1 1Emergency Department, West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Medical Intensive Care Unit, West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Operations Management Department, West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Cao, Emergency Department, West China Hospital of Sichuan University, 37 Guoxue Lane, Wuhou District, Chengdu, Sichuan, 610041, People’s Republic of China, Tel +86 28-85422288, Email caoyu@wchscu.cnPurpose: The thrombo-inflammatory prognostic score (TIPS) and the bedside index for severity in acute pancreatitis (BISAP) are both scoring systems that enable the rapid prognostic assessment of early-stage acute pancreatitis (AP) patients, but the overall prognostic utility of these individual systems is limited. This study was thus developed to explore whether a combination of TIPS and BISAP scores would offer better insight to facilitate the risk stratification of AP patients.Methods: This single-center retrospective cohort research evaluated AP cases referred to the emergency department from January 1, 2017 to September 30, 2017. The ability of TIPS scores to improve BISAP-based AP patient risk stratification was appraised employing the curves of receiver-operating characteristic (ROC) and decision curve analysis (DCA) approaches. The initial endpoint for this research was 28-day mortality, while secondary endpoints comprised intensive care unit admission (AICU) and mechanical ventilation (MV) over a 28-day follow-up period.Results: Totally, 440 cases enrolled in the current study were divided at a ratio of 1:1 to derivation and validation cohorts. When estimating 28-day mortality, the combination of TIPS and BISAP (T-BISAP) improved the area under the curve (AUC) value in the derivation group from 0.809 to 0.903 (P